IMPLEMENTATION AND ORGANIZATION OF THE CIRCLE RESEARCH AND DEVELOPMENT SOFTWARE AND AUTOMATION - CIDESOFT - Raffo L., Eduardo (2002)
In the present writing, the analysis, desing and implementation of the On-Line Job Section is described, which is a project comprised by the UNMSM-INDUSTRIAL PORTAL. For the development of this project, the methodology proposed by Software Engineering is used, employing up-to-date modelling and analysis tools. It is in addition the UNMSM-Faculity of Industrial Engineering Data WareHousing's implementation. It is furthermore pointed out that project was developed with the help of CIDESOFT.